G191(P) All that presents with spastic gait may not have cerebral palsy. (May 2019) - Misra, S; Sinha, G; Gupta, R; Verma, P
Abstract : We report a case of probable Hereditary Spastic Paraplegia (HSP), a rare condition with an estimated prevalence of 3 in 1 00 000. HSP is a group of genetically variable disorders that can manifest in different ways clinically but has a characteristic symptom of lower limb spasticity. It raises some fundamental questions around the importance of basic clinical skills and limitations of diagnostic tests. Advancements in genetic testing has helped in recognizing many of these patients. This 7-year-old boy presented to the Paediatric clinic with an increased frequency of toe-walking and pain in his legs in cold weather. On examination, he had a spastic diplegic gait, hypertonia and hyperreflexia of both lower limbs and ankle clonus. Power was normal, and he was able to perform anti-gravity movements. Plantar responses were up-going. He was born at term by emergency C-section for foetal distress. No resuscitation was required. At 14 months, he could stand with in turning of his ankles and gradually preferred walking on his toes and would trip easily. Other aspects of his development were normal. At 18 months, he was diagnosed with flat feet and tight tendon Achilles for which he was referred to physiotherapy and orthotics and discharged from Paediatric follow up. His mother also had similar difficulties since childhood and was under physiotherapist care. Her MRI head and spine were normal. On examination, she had an abnormal gait with hypertonia and hyperreflexia in both lower limbs. His Blood and urine tests including creatinine kinase and metabolic tests were normal. MRI head, spine, nerve conduction studies and EMG were normal. Initial SPAST gene analysis is negative, however complete analysis is awaited. Despite the experience of doctors and availability of advanced diagnostic tests, accurate diagnosis continues to elude us on occasions such as this. Advancements in genetic testing may eventually allow for pre-symptomatic or even antenatal diagnosis but for now exclusion of other diagnosis such as cerebral palsy remains key. Finally, a thorough examination and comprehensive capture of family history can be a substantive starting point of diagnosis and should be done more completely at an early stage of the assessment.